A History of Modern Press Access to the Supreme Court of the United States. Issue 4 (14th October 2021) - Kimball, Michele Bush
Abstract : Throughout its history, the Supreme Court of the United States has allowed members of the press access to oral arguments and decision releases in its courtroom. However, it took nearly eighty years to formally codify a process by which members of the press were officially credentialed to cover the Court, a pass giving them access to the courtroom beyond the bar, access to walk the halls freely, to work in dedicated space in the building, and access to the justices themselves. This article traces the history of the press credentialing from the day the justices moved into the Supreme Court building in Washington, D.C., in 1935 to the unprecedented public access granted to oral arguments due to the social distancing required by the COVID19 virus in the spring of 2020. It is meant to fortify the historical record to ensure that the Court remains as open and accessible as possible to reporters because they act as emissaries of the public. The Court's decisions affect all aspects of life for citizens, and therefore public knowledge of the Court's work is essential to a strong democracy. Press access is key to that understanding.